Comparative Silk Transcriptomics Illuminates Distinctive Impact of Artificial Selection in Silkworm Modern Breeding - Kesen Zhu; Yanfei Chen; Lei Chen; Hui Xiang (Insects, 2022)
Early domestication and the following improvement are two important processes in the cocoon silk evolution of silkworms. In contrast to early domestication, understanding of the improvement process is still fuzzy. By systematically comparing the larval silk gland transcriptomes of the wild, early domestic, and improved silkworms, we highlighted a novel landscape of transcriptome in the silk glands of improved ones. We first clarified that silk cocoon protein genes were up-regulated in modern breeding but not in early domestication. Furthermore, we found that differentially expressed genes (DEGs) between improved and early domestic silkworms (2711), as well as between improved and wild silkworms (2264), were obviously more than those between the early domestic and wild silkworms (158), with 1671 DEGs specific in the improved silkworm (IS-DEGs). Hierarchical clustering of all the DEGs consistently indicated that improved silkworms were significantly diverged from the early domestic and wild silkworms, suggesting that modern breeding might cause prompt and drastic dynamic changes of gene expression in the silk gland. We further paid attention to these 1671 IS-DEGs and were surprised to find that down-regulated genes were enriched in basic organonitrogen compound biosynthesis, RNA biosynthesis, and ribosome biogenesis processes, which are generally universally expressed, whereas those up-regulated genes were enriched in organonitrogen compound catabolic processes and functions involving in the dynamic regulation of protein post-translation of modification. We finally highlighted one candidate improvement gene among these up-regulated IS-DEGs, i.e., GDAP2, which may play roles in silk behavior and the overall robustness of the improved silkworm. The findings strongly suggest that modern breeding may facilitate effective control of the basic consumption of nitrogen and a stronger switch of nitrogen resources from other tissues to the silk glands, for an efficient supply for silk production, and implies the importance of brain behavior and robustness in silk yield improvement of modern breeding.